2013 IEEE International Symposium on Industrial Electronics 2013
DOI: 10.1109/isie.2013.6563753
|View full text |Cite
|
Sign up to set email alerts
|

Haptic bilateral control system with visual force compliance controller

Abstract: This paper presents a new haptic bilateral control method with vision-based guidance. The vision-based guidance is realized by the visual force compliance controller which can translate the visual information to assistive force. Integration of an imaging modality effectively further consolidates the servoing procedures. Such information needs to be efficiently rendered to the operator at master system. Particularly, the proposed approach provides real-time visualization and force feedback based guidance for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…The conventional web camera [15] with the maximum resolution of 1280 × 1024 pixels and 30 fps frame rates is used as a vision sensor. It is mounted on the camera stand with the facing down direction, so that it can monitor the moving object from above.…”
Section: ) Object Detectionmentioning
confidence: 99%
See 2 more Smart Citations
“…The conventional web camera [15] with the maximum resolution of 1280 × 1024 pixels and 30 fps frame rates is used as a vision sensor. It is mounted on the camera stand with the facing down direction, so that it can monitor the moving object from above.…”
Section: ) Object Detectionmentioning
confidence: 99%
“…The detection of the object is considered by implementing the image processing [15] to detect the object marker pasted on the object. The object marker used in this research is a simple blue color of line marker as shown in Fig.…”
Section: ) Object Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The horizontal movement of the navigated object had been considered by the compliance controller to produce the dedicated virtual force [6]. In other related visual and haptic feedback study, the model-displaced teleoperation (MDT) approach was proposed by [7] to compensate the visual-haptic asynchrony issue.…”
Section: Introductionmentioning
confidence: 99%
“…The vertical movement of an object had been highlighted in the research. However, both studies [6], [7] did not consider the rotational effect of the measured object in its trajectory movement. Thus, a method that emphasizes the trajectory alteration of the object and its effect on the haptic bilateral system, need to be developed.…”
Section: Introductionmentioning
confidence: 99%